I’dad Al-Kitabi At-Ta’limiy Li Maaddati Al-Khatti Al-Arabiy Bi Ma’had Al-Mukhlishin Batu Bara Sumatera Asy-Syamaliyah - Ainul Mardiah (Department of Arabic Teaching, Faculty Tarbiyah, Universitas Darussalam Gontor, 2021)
This study aims to develop an Arabic calligraphy textbook based on Khaṭṭ al-Naskh, evaluate its validity, and examine its effectiveness in improving students’ calligraphy skills at Al-Mukhlisin Islamic Boarding School, Batu Bara, North Sumatra. The study was motivated by the limited availability of instructional materials for Arabic calligraphy, which resulted in students’ low proficiency. In practice, teachers relied on scattered learning resources rather than a structured textbook, making the learning process less systematic and limiting students’ opportunities to practice independently outside the classroom. To address this problem, the researcher developed a Khaṭṭ al-Naskh textbook as the primary learning resource. Khaṭṭ al-Naskh was selected because it is one of the most widely used Arabic scripts, recognized for its clarity, readability, and suitability for beginners. The study employed a Research and Development (R&D) approach using the Borg and Gall model. Data were collected through observation, interviews, questionnaires, tests, and documentation. The developed textbook was evaluated through expert validation, while its effectiveness was measured using a pre-test and post-test design involving female students at the Al-Mukhlisin Islamic Boarding School. The findings indicate that the research successfully produced a textbook for teaching Arabic calligraphy based on Khaṭṭ al-Naskh. Expert validation demonstrated that the textbook was highly feasible for instructional use, achieving a validity score of 89.3%. Furthermore, the effectiveness test revealed a t-value of 7.863, which exceeded the critical t-table value of 2.000 at the 5% significance level. These results confirm that the developed textbook significantly improves students’ Arabic calligraphy skills and can serve as an effective instructional resource for Arabic calligraphy learning in Islamic boarding schools.